Fortschritte beim vorsorgenden Hochwasserschutz durch die Raumordnung: Nationale und transnationale raumordnerische Ansätze am Beispiel der europäischen Flussgebiete des Rheins und der Oder - Heiland, Peter; Dapp, Klaus (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
The task of flood prevention is one which concerns society in its entirety. The role of comprehensive spatial planning, both in making available the land required and in supporting preventive action, is now beyond dispute. Indeed, for over ten years a pro-active policy of integrating flood-prevention measures within spatial-planning practice has been pursued and advanced with ever-increasing intensity. This article seeks to establish just what concrete advances are now visible, both in spatial planning within Germany and in the context of transnational co-operation. It concludes by setting out a number of further steps either currently being implemented, or which will become necessary in the future.